(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract: Intensive therapy in the postoperative period following neuro-oncological surgeries aims to reduce cerebral edema and protect cells from hypoxia and oxidative damage. This article provides a comprehensive analysis of the neuroprotective properties of dexmedetomidine, sodium oxybutyrate, and osmodiuretics, as well as their application and combined effectiveness. Dexmedetomidine, with its sympatholytic and anti-inflammatory effects, contributes to improved cerebral blood circulation. The efficacy of dexmedetomidine in lowering arterial pressure and providing neuronal protection further broadens its application. Considering its role in strengthening the blood-brain barrier, its use in neurosurgery marks a new dimension of its efficacy. The clinical advantages of dexmedetomidine in reducing postoperative complications are highly valued due to the aforementioned factors. This article presents a detailed analysis of the outcomes of using dexmedetomidine, sodium oxybutyrate, and osmodiuretics in intensive therapy following neuro-oncological surgery.